Pengaruh In-Store Display, Bonus Pack Dan Discount Terhadap Impulse Buying Pada Iwan Swalayan Tenggarong - Raharjo, Sugeng; Sari, Nilam Anggar; Sapitri, Reski Nur (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2020)
Abstract : This study aims to determine and analyze the magnitude of the influence of In-Store Display, Bonus Pack and Discounts on Impulse Buying at Iwan's swalayan in Tenggarong. Respondents who were involved in this study were 94 respondents, while the method used in this study was probability sampling. Namely in-store displays, bonus packs and discounts with 1 dependent. Data collection was carried out by distributing questionnaires and the method of analysis used in this study was multiple linear regression with the help of the SPSS 25 statistics. Based on the results of testing the first hypothesis regarding the variable in store display, bonus and discount, the effect is received simultaneously. The findings indracle that bonus pack had a partical and significant effect on impulse buying. In store display variables had no significant effect on impulse buying. The second hypothesis regarding the in store display, the results are rejected with the value (t count = -0.752 < t table = 1.987). the third hypothesis regarding the bonus pack, the result is accepted with the value ( t count = 5.257 > t table= 1.987), the fourth hypothesis regarding the discount is rejected with the value (t count = 0.773 < t table = 1.987). The fifth hypothesis regarding the bonus pack has a dominant effect on impulse buying at iwan swalayan was accepted and proven to be true. Keywords: In-Store Display, Bonus Pack, Discount , Impulse Buying